EUPHEMISM USED BY MEN AND WOMEN IN ‘INDONESIA LAWYERS CLUB’ TV ONE SHOW: A LANGUAGE AND GENDER PERSPECTIVE - Meci Fitriani; Hermawati Syarif; Delvi Wahyuni (Universitas Negeri Padang, 2019)
This research describes about how men and women used euphemism in ‘Indonesia Lawyers Club’ TV One show which limited to the types and functions of euphemism used by men and women. The source of data was obtained from transcript of the 4 videos aired on December 2017, Januari 208 and February 2018. From the analysis, there were 72 utterances contain euphemistic expression, 33 utterances delivered by men and 39 remarks spoken by women. In this show researcher found 9 types of euphemism, namely: metaphor, hyperbole, circumlocution, initialism, jargon, figurative expression, understatement, colloquial, and hypernym. From the types mention above, men mostly used euphemism in the type of understatement while women mostly prefer to use jargon. Furthermore, researcher found 5 function of euphemism in this show; euphemism as doublespeak, as a shield to avoid taboo and offense, as uplifting tool, to show solidarity or define certain group, and to entertain.